Thirteenth Canadian Geotechnical Colloquium: Ice design criteria for wide arctic structures - Blanchet, Denis (Canadian Geotechnical Journal, 1990)
The derivation of design global ice loads for wide vertical caisson-type arctic exploration structures is presented. Correction factors are applied to global ice-load data measured during ice–structure interactions to create a set of design criteria for two typical exploration structures: circular (100 m diameter) and rectangular (160 × 50 m). Return periods for the proposed deterministic design ice loads for these two structures are then determined for typical ice conditions encountered in the Harrison Bay shear zone area in 20–30 m of water. Key words: exploration structures, global design ice loads, risk, probability of exceedence, return periods.